Adsorption of dihydrogen phosphate ion on platinum electrodes in aqueous media monitored by probe-beam deflection - Bidoia, Ederio Dino [UNESP] (Elsevier, 2005)
Probe-beam deflection (PBD) was used to monitor concentration gradients of anions adjacent to the surface of a platinum electrode in acidic aqueous media containing H3PO4. PBD can measure the potential-dependent extent of adsorption of H2PO4- on the Pt electrode surface and permits the Langmuir isotherm to be fitted to the experimental data. The value thus obtained for the surface concentration was 1.3 × 10-11 mol mm -2, or 1.7 atoms of Pt per H2PO4-. Also, the electron transfer number obtained was 0.24, signifying an incomplete transfer of charge, and the equilibrium constant is 1.80 suggesting a reversible adsorption process. © 2005 Elsevier B.V. All rights reserved.
Keywords: Adsorption; Charge transfer; Electrodes; Negative ions; Phosphates; Platinum; Solutions; Spectrometers; Anion adsorption; Dihydrogen; Electrode surfaces; Probe-beam detection; Ions